5‐(2‐Aminopropyl)indole (5‐IT): a psychoactive substance used for recreational purposes is an inhibitor of human monoamine oxidase (MAO). Issue 7 (20th September 2013) - Herraiz, Tomás; Brandt, Simon D.; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> 5‐(2‐Aminopropyl)indole (5‐IT) is a psychoactive compound that has recently been associated with several fatal and non‐fatal intoxications in a number of European countries. There are indications that acute effects may include symptoms of monoaminergic (e.g. serotonin) toxicity and one mechanism involved in the increase of serotonin levels includes the inhibition of monoamine oxidase. This study investigated the effect of 5‐IT on human MAO‐A and ‐B isozymes using kynuramine as the substrate. Substrate conversion to 4‐hydroxyquinoline was monitored by high‐performance liquid chromatography coupled to diode array detection. This method was employed to determine the extent of MAO inhibition (IC50 and Ki) and it was found that 5‐IT was a selective, competitive and reversible inhibitor of MAO‐A. 5‐IT revealed a relatively potent ability to inhibit MAO‐A (IC50 = 1.6 μM and Ki = 0.25 μM) while MAO‐B inhibition was not observed (0–500 μM 5‐IT). Under identical experimental conditions, other established inhibitors of MAO‐A and antidepressants provided the following IC50 values: clorgyline 16 nM, harmaline 20 nM, toloxatone 6.7 μM and moclobemide >500 μM. These data indicated that 5‐IT was less potent than clorgyline and harmaline but more potent than toloxatone and moclobemide under the in‐vitro conditions studied. The inhibition of MAO‐A suggests that 5‐IT by itself or in combination with other substances may be able to potentiate serotonergic/monoaminergic effects and further studies are needed to clarify its relevance to the adverse effects reported for 5‐IT. Copyright © 2013 John Wiley & Sons, Ltd.